Software Defi ned Satellite Network Assisted Multi-Domain Routing Strategy for Aeronautical Networks - Mo SHA; Kaixuan SUN; Huasen HE; Wenke YUAN; Zhicheng YE; Jian YANG (天地一体化信息网络)
Satellite network layer and aeronautical network layer are treated as important parts of the next generation network, which will lead the world into the era of global interconnection.However, the high mobility and sparse distribution of aircraft limit the application of traditional routing algorithms originally designed for ground-based ad-hoc networks.Therefore, this paper used the aeronautical network to access software defi ned satellite network (Sat-SDN) for realizing real-time communication and state synchronization between aircraft via the inter-satellite and satellite-to-aircraft links.In order to extend the aeronautical networking and transmission mechanism to the global scope, a multiple domain division method was proposed, and an inter domain routing algorithm was presented.By analogy the refl ection principle of light, a routing learning method which limited the broadcasting of routing learning packets into a specifi c area was proposed, and eff ectively avoided severe communication overhead caused by state synchronization and fl ooding learning in large-scale networks.The real aircraft data was used for experimental simulation to compared the performance of proposed low-cost inter-domain routing algorithm (LIRA) with existing solutions.The simulation results showed that LIRA could eff ectively reduced the communication overhead and improved the transmission quality.